THE HEMOSTASIS SYSTEM STATUS IN CHILDREN WITH METABOLIC SYNDROME - N. A. Tsaregorodtsev; O. V. Ivanova; O. A. Dianov (Бюллетень сибирской медицины)
The aim of the research was to study the characteristic properties of hemostasia system of children suffer-ing from metabolic syndrome (MS) and exogenous obesity.Material and methods, A total of 58 children and adolescents aged from 9 to 16 with different stages of obesity. The examined were divided into two groups – the main group including children with MS (n = 33) and the control group including patients with exogenous obesity but without any indications of (n = 25). The presence of obesity was stated according to the criteria described by L.V. Kozlova and her co-authors (2008). All the examined patients had a biochemical blood analysis that included component determination of hemostasia system. The component determination was to reflect all the links of blood coagulation, so the following indices were analysed – activated partial thromboplastin time (A-PPT), prothrombin time (PTT), prothrombin ratio, level of fibrinogen, thrombin time, international normalized ratio (INR) and thrombocyte aggregation with ristomycin.Results. The children suffering from MS compared with the children without this syndrome had signifi-cantly higher level of prothrombin time, thrombocyte aggregation with ristomycin as well as INR. The index of thrombocyte aggregation with ristomycin in the main group was not only higher than in the con-trol group but also exceeded the reference value. The boys with MS had a notably higher index of throm-bocyte aggregation with ristomycin than the boys suffering fron obesity. The girls with MS had a higher INR factor than the group of girls with obesity.Conclusions. The research showed that with children suffering from MS their hemostatic system gets involved in the pathological process. The discovered peculiarities show inclination to hyper-coagulation